WHAT IS AN IMPORTANCE OF ACCENT? DIFFERENCES BETWEEN AMERICAN AND BRITISH ACCENT. - Ashurova Gulbeka Alisher qizi (TADQIQOTLAR.UZ, 2024)
This article investigates the general concept of accent. In addition, it shows how important the accent is in the process of speaking and how much attention should be paid for using it correctly. Moreover, it also acquires knowledge of the general information about American and British accents and the differences between them.